DUKUNGAN SOSIAL DAN PSYCHOLOGICAL WELL-BEING PADA GURU TK SAAT PANDEMI COVID-19 - Nagari, Marceline Joana Tyas Laksmi; Hapsari, Elisabet Widyaning (Fakultas Psikologi Universitas Hang Tuah, 2023)
Abstract. The Covid-19 pandemic has had an impact on education, causing a switch from conventional learning to distance (online) learning. This change in the learning model has put special pressure on teachers, especially kindergarten teachers. This research aimed to examine the relationship between social support and psychological well-being in kindergarten teachers during the Covid-19 pandemic. Research respondents were kindergarten teachers (N = 85) in Surabaya selected using purposive sampling techniques. The scales used were the social support scale and psychological well-being scale compiled by the researchers. The research results showed a positive relationship between social support and psychological well-being in kindergarten teachers during the Covid-19 pandemic. The other results showed that the higher the social support from colleagues, the higher the psychological well-being of kindergarten teachers.